Mindfulness-based focused attention training versus progressive muscle relaxation in remitted depressed patients: effects on salivary cortisol and associations with subjective improvements in daily life - Beddig, Theresa; Timm, Christina; Ubl-Rachota, Bettina; Zamoscik, Vera; Ebner-Priemer, Ulrich; Reinhard, Iris; Kirsch, Peter; Kühner, Christine (Psychoneuroendocrinology, 2020)
Major Depression is a stress-related disorder characterized by altered hypothalamic-pituitary-adrenal axis function. Mindfulness-based interventions have shown to improve subjective parameters of stress and to reduce relapse rates in depressed patients. However, research on their effects on diurnal patterns of cortisol and associations with subjective outcomes is lacking. The present Ambulatory Assessment study investigated possible changes in daily rhythm cortisol parameters (cortisol awakening response (CAR), daily slope, total cortisol) in currently remitted individuals with recurrent depression who were randomized to a four-week mindfulness-based focused attention training (MBAT, n = 39) or a progressive muscle relaxation training (PMR, n = 39). A second aim was to investigate whether changes in cortisol were linked to improvements in affective and cognitive daily life states. On three weekdays before and after the intervention, seven saliva cortisol samples per day were collected. For analysis, multilevel models were applied. Results revealed no group-specific or general change in CAR and daily slopes from pre- to post-intervention. In contrast, total cortisol increased across groups, which was however moderated by group and subjective improvement status. While cortisol increased irrespective of subjective improvement in PMR participants, MBAT participants with larger reductions in negative affect and rumination maintained their initial cortisol levels, whereas those with lower improvement paralleled the PMR group. Thereby, MBAT appeared to buffer an increase in overall cortisol secretion over time, but only in patients showing marked improvements in those affective and cognitive states that constitute core elements for depressive relapses in the vulnerability model of mindfulness-based cognitive therapy.